Polimorfismos no gene do hormônio do crescimento em linhagens de codorna (coturnix japonica) e sua associação com características de desempenho - Marques, Débora Sommer (2009)
Genetic studies with quails are less frequent than those with broiler or layer hicken. The growth hormone (GH) plays a fundamental role on the birds' development. The GH affects egg production and participates on the development of bone and skeletal muscle, stimulating muscle growth, thus making GH a very well studied candidate gene. On many species, polymorphisms have been identified in the GH gene and have been associated to characteristics of interest. This work had the objective of studying a fragment of the growth hormone gene on different lineages of quails (three layer lineages and one broiler lineage), generating unpublished sequences by automatic sequencing and the use of free software of nucleotide sequence analysis to verify polymorphisms, as well as enabling the use of this information in improvement programs. Another objective of this work was to detect GH gene polymorphisms in quails, using the PCR-RFLP technique and associate these polymorphisms to performance and carcass traits. For this, 200 quails (Coturnix japonica), belonging to two genetic groups (broiler lineage and crossing between layer x broiler lineages) were analyzed. It was observed high similarity (85%) among the sequenced fragments and the sequence of the same gene on chicken, although it was verified punctual mutations as transversions and transitions, and also deletions and insertions of bases. Among quails lineages were verified 20 polymorphisms, mostly located on intro regions. However, on the region 5´UTR of the exon 1, it was detected an important polymorphism (C/T), which can be used on several studies of associations with economical interest characteristics, because in other species, polymorphisms on this same region indicated an association with production characteristics. Using the PvuII enzyme, three genotypes where found (C/C, C/T and T/T) for the T_C polymorphism. The broiler lineage presented the three distinct genotypes and the higher frequency was observed for the heterozygote (C/T), 48.52%, while the crossing lineage presented only two genotypes (C/C,C/T). The variance analysis revealed significant association between marking genotypes (GH-PvuII) and the RP on the males of the crossing lineage, with the highest average for the genotype C/C (41.05 g + 2.35%). On this study were also observed the effects of the marking genotype (GH-PvuII) on the characteristics H and UH, being the genotype C/C the one that presented the highest average for the characteristics (5.64 ± 0,71 mm and 94.66 ± 3.26, respective.